Review on Major Assisted Reproductive Technologies (Global Journal of Science Frontier Research, 2017)
Since early period, several reproductive technologies practiced as a prime concern for researchers, employed for genetic improvement of farm animals. This review deals with the assisted reproductive technologies (ARTs) among the known approaches for genetic improvements. This review paper focused on artificial insemination (AI), estrus synchronization, multiple ovulation and embryo transfer (MOET), cryopreservation (freezing) of gametes or embryos and in vitro embryo production (IVEP). Briefly to see, AI is the manual placement of semen in the reproductive tract of the female by a method other than natural mating. AI is the most effective method being used for the genetic improvement of animals. Estrous synchronization is another process of targeting female mammals to come to heat within a short time frame (36 to 96 hours) that is to have a number of females in estrus during a very short period.
Keywords: ART; AI; assisted; technologies; IVEP